Hukum dan Kebijakan Publik dalam Ketertiban Umum: Analisis Normatif, Empiris, dan Implikasi Kebijakan di Indonesia - Syahri Ramdhani; Holijah Holijah (Interdisciplinary Explorations in Research Journal, 2026)
Public order is a fundamental prerequisite in a democratic rule-of-law state. In Indonesia, law and public policy play complementary roles in maintaining social stability and protecting citizens’ rights. This study aims to analyze the relationship between law and public policy in ensuring public order and to evaluate implementation challenges. This research employs a normative juridical method combined with conceptual and statutory approaches, supported by limited empirical observations. The findings indicate that the effectiveness of public order depends on the integration of strong legal norms and adaptive, participatory public policies. Weak institutional coordination and inconsistent law enforcement remain major obstacles.